Internationalisation of Higher Education: International students’satisfaction. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)
Malaysia aspires to be an international education hub and in achieving this, the Malaysian Ministry of Higher Education (MoHE) then, has put in place internationalisation of higher education as one of the strategic trusts as stipulated in Malaysia National Strategic Plan of Higher Education (PSPTN) Phase 1 (2007-2010).